2018
DOI: 10.1155/2018/3506874
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Detection of EMT Markers in Circulating Tumor Cells from Metastatic Non-Small Cell Lung Cancer Patients: Potential Role in Clinical Practice

Abstract: Background Non-small cell lung cancer (NSCLC) is the most common cause of cancer-related mortality; nevertheless, there are few data regarding detection of circulating tumor cells (CTCs) in NSCLC, compared to other kinds of cancers in which their prognostic roles have already been defined. This difference is likely due to detection methods based on the epithelial marker expression which ignore CTCs undergoing epithelial-mesenchymal transition (CTCsEMT). Methods After optimization of the test with spiking exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 51 publications
0
24
0
Order By: Relevance
“…During the dynamic testing, the expression of the mesenchymal phenotype appeared to be associated with a more unfavorable prognostic factor. However, the clinical significance of the EMT phenotypic CTC needs to be further validated considering the limited patient number in the study by Milano et al (36). In the present study, 110 patients (85 patients with NSCLC from different clinical stages and 25 patients with benign diseases) were recruited.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…During the dynamic testing, the expression of the mesenchymal phenotype appeared to be associated with a more unfavorable prognostic factor. However, the clinical significance of the EMT phenotypic CTC needs to be further validated considering the limited patient number in the study by Milano et al (36). In the present study, 110 patients (85 patients with NSCLC from different clinical stages and 25 patients with benign diseases) were recruited.…”
Section: Discussionmentioning
confidence: 94%
“…Thus, the expression of epithelial cell markers including EpCAM and members of CKs are downregulated and that of mesenchymal cell markers is upregulated (14)(15)(16)35). Milano et al (36) designed a study to detect the EMT of CTCs in patients with metastatic NSCLC and analyzed the expression of epithelial markers (carcinoembryonic antigen-CK19), EMT-associated genes (vimentin) and EMT transcription factors (zinc finger protein SNAI2, zinc finger E-box-binding homeobox 1-2 and TWIST1-2) using a reverse transcription-polymerase chain reaction assay in order to calculate the cell numbers. However, in the present study, RNA in situ hybridization with a combination of epithelial (EpCAM and CK8/18/19) and mesenchymal (vimentin and TWIST1) markers were used to detect the epithelial and mesenchymal phenotype of CTCs, and an automated imaging fluorescent microscope was used to directly count the cells with different phenotypes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While CTC analyses have typically relied upon selection of epithelial-phenotype CTCs via EpCAM, CK, or other epithelial markers, mesenchymal-and mixed epithelial/ mesenchymal-phenotype CTCs are, a priori, more consistent with the characteristics of metastatic tumor cells, including enhanced motility, invasiveness, and self-renewal [42]; indeed, data from several recent studies across multiple tumor types have suggested that mesenchymal-or mixed E/M-phenotype CTCs may be of greater prognostic and/or predictive value than their epithelial-phenotype counterparts [24][25][26][27]. Following the emergence of this information regarding the potential predictive value of mesenchymal-or mixed E/M-phenotype CTCs, we developed and validated a novel custom CellSearch ® assay to assess p16 expression in the putative mixed E/M-phenotype subpopulation.…”
Section: Characterization Of Vimentin-positive Ctcsmentioning
confidence: 94%
“…Initially, we focused this analysis on epithelial-phenotype (cytokeratin-positive, putatively EpCAM-expressing) CTCs. However, during the course of the trial, new knowledge came to light regarding the biological relevance and potential prognostic value of mesenchymal-and mixed epithelial/mesenchymal (E/M)-phenotype CTCs in patients with metastatic disease [24][25][26][27]. Therefore, we developed and validated a novel 5-channel CellSearch ® assay to assess treatment-induced changes in p16 expression in the putative mixed E/M-phenotype (vimentin-positive, putatively EpCAM-expressing) CTC subpopulation for patients who enrolled during the final years of the study, after validation of this assay for E/M-phenotype CTCs had been completed.…”
Section: Introductionmentioning
confidence: 99%